2020
DOI: 10.3892/mmr.2020.10959
|View full text |Cite
|
Sign up to set email alerts
|

A six‑gene support vector machine classifier contributes to the diagnosis of pediatric septic shock

Abstract: Septic shock is induced by an uncontrolled inflammatory immune response to pathogens and the survival rate of patients with pediatric septic shock (PSS) is particularly low, with a mortality rate of 25-50%. The present study explored the mechanisms of PSS using four microarray datasets (GSe26378, GSe26440, GSe13904 and GSe4607) that were obtained from the Gene Expression Omnibus database. Based on the MetaDE package, the consistently differentially expressed genes (DEGs) in the four datasets were screened. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…Consistent with our results, Guoli et al. also found that UPP1 was highly expressed in children with septic shock ( 30 ). These suggested that UPP1 may involve in young sepsis patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our results, Guoli et al. also found that UPP1 was highly expressed in children with septic shock ( 30 ). These suggested that UPP1 may involve in young sepsis patients.…”
Section: Discussionsupporting
confidence: 93%
“…Mike et al reported that the expression of UPP1 was up-regulate in young sepsis rat when compared with aged sepsis rat (29). Consistent with our results, Guoli et al also found that UPP1 was highly expressed in children with septic shock (30). These suggested that UPP1 may involve in young sepsis patients.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, WGCNA applied to sepsis may show potential beyond traditional clinical biomarkers. For example, LONG et al combined WGCNA with a machine learning algorithm and applied this work ow to three publicly available sepsis datasets [23]. Then by applying arti cial intelligence concepts to WGCNA, Long et al presented a diagnostic classi er with the potential for early diagnostic bene t.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset contained 29 instances of survival class (23) and non-survival class (6), which was an unequal distribution of classes. In machine learning, unequal data distribution is one of the major causes of decreasing accuracy of classi cation models.…”
Section: Machine Learning Data Processing and Methodsmentioning
confidence: 99%